Adams, Bernice Phonnie. Oral history interview, May 15, 1994. - Adams, Bernice Phonnie (Valdosta State University Archives and Special Collections, 1994)
Adams, Bernice Phonnie. Oral history interview, May 15, 1994. Camilla, Georgia. Interviewed by Jana Godwin. David Williams Oral History Collection: Personal Accounts of the Great Depression in South Georgia. Valdosta State University Archives and Special Collections.
1 electronic record, includes audio files, transcript files and a photograph.
Keywords: Oral histories; Depressions--1929--United States; Great Depression; Camilla (Ga.); Mitchell County (Ga.)